2015
DOI: 10.1017/ice.2015.32
|View full text |Cite
|
Sign up to set email alerts
|

The Perennial Problem of Variability In Adenosine Triphosphate (ATP) Tests for Hygiene Monitoring Within Healthcare Settings

Abstract: The variability of commercial ATP bioluminometers and their consumables is unacceptably high with the current technical configuration. The advantage of speed of response is undermined by instrument imprecision expressed in the numerical scale of relative light units (RLU).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 34 publications
0
25
0
2
Order By: Relevance
“…Notably, except in a few studies [ 7 , 9 ], the threshold of the ATP-assay results used to indicate cleanliness was not calibrated according to the sampling area. The RLU value that is obtained using the ATP assay is a relative unit that has not been quantified against known standards [ 10 ]. Similar to culture level values, the measured ATP levels should be proportional to the sampling area, and if the ATP readings are obtained without calibration of the sampling area, the values will be difficult to interpret and the correlation with ACC assay–based values will decrease.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, except in a few studies [ 7 , 9 ], the threshold of the ATP-assay results used to indicate cleanliness was not calibrated according to the sampling area. The RLU value that is obtained using the ATP assay is a relative unit that has not been quantified against known standards [ 10 ]. Similar to culture level values, the measured ATP levels should be proportional to the sampling area, and if the ATP readings are obtained without calibration of the sampling area, the values will be difficult to interpret and the correlation with ACC assay–based values will decrease.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the work of Reed et al a Cv of 0.4 suggests that any two measures from the identical surface could differ by a factor of 1.5 or more in nearly half of all trials and differ by a factor of 2 or more in 1 in every 5 trials [23]. In such cases, a reading of 50 RLU and 100 RLU could be generated from the same surface cleanliness and still represent the same result [24,25]. While a Cv of 0.4 was relatively infrequent, our proposed algorithm is conservative and based on the possible two-fold difference in RLU measures.…”
Section: Methods the Atp Testing Algorithmmentioning
confidence: 99%
“…Controlled experiments have demonstrated that a Cv of 0.4 is a frequent occurrence [24]. In studies using a single sampling point, where the Cv is above 0.4, there is a 20% chance that any reading could be wrong by a factor of two [25].…”
Section: Variability and Imprecision With Atp Testingmentioning
confidence: 99%
“…We will routinely assess bio-burden on a selection of high touch surfaces using adenosine tri-phosphate (ATP) luminosity following cleaning in three of the 11 hospitals, using a validated sampling process [ 27 ].…”
Section: Methodsmentioning
confidence: 99%